2019
DOI: 10.1021/jacs.8b13498
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Aromatic Monomers as Building Blocks To Control α-Peptoid Conformation and Structure

Abstract: Peptoids are peptidomimetics of interest in the fields of drug development and biomaterials. However, obtaining stable secondary structures is challenging, and designing these requires effective control of the peptoid tertiary amide cis/trans equilibrium. Herein, we report new fluorine-containing aromatic monomers that can control peptoid conformation. Specifically, we demonstrate that a fluoro-pyridine group can be used to circumvent the need for monomer chirality to control the cis/trans equilibrium. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…Recent studies suggest that both PPII and trans ‐peptoids are stabilized by n → π* interactions (Figure B and C), as evidenced by the short O (i–1) ··· C' ( i ) =O distances (≤ 3.2Å) and angles around 109° ± 10°. On the other side, PPI and cis ‐peptoids are stabilized by favorable N C α –H ··· O=C eclipsing (due to n → σ* orbital overlap between carbonyl and side chain methyne/methylene hydrogen atoms), and general inductive/dipolar effects , . It has also been also showed that weak backbone C α –H ··· O=C, and side chain London interactions play an important role in the general stabilization of secondary structures , …”
Section: Synthesis and Structural Properties Of Cyclic Peptoidsmentioning
confidence: 99%
“…Recent studies suggest that both PPII and trans ‐peptoids are stabilized by n → π* interactions (Figure B and C), as evidenced by the short O (i–1) ··· C' ( i ) =O distances (≤ 3.2Å) and angles around 109° ± 10°. On the other side, PPI and cis ‐peptoids are stabilized by favorable N C α –H ··· O=C eclipsing (due to n → σ* orbital overlap between carbonyl and side chain methyne/methylene hydrogen atoms), and general inductive/dipolar effects , . It has also been also showed that weak backbone C α –H ··· O=C, and side chain London interactions play an important role in the general stabilization of secondary structures , …”
Section: Synthesis and Structural Properties Of Cyclic Peptoidsmentioning
confidence: 99%
“…Due to their highly electron deficient nature, perfluoroaromatics can have significant effects on the electronics of molecular systems [ 60 ]. Perfluoroaromatic moieties have therefore seen use in materials [ 61 ], catalysis [ 62 , 63 ] and organic synthesis [ 64 , 65 ], and have been exploited in peptide [ 66 , 67 ] and peptoid chemistry [ 68 ]. Access to highly fluorinated amino acids is therefore an area of much research, with several reports detailing the synthesis of aromatic perfluorinated amino acids.…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%
“…The emergence of fluorine in drug design highlighted the potential of fluorinated amino acids, peptides and mimetics, and the possibility to tailor their geometry with such a peculiar element . In particular, proline surrogates, which were fluorinated or trifluoromethylated in their lateral chain, were examined as useful conformational tuning tools that allowed fine control of the cis ‐ or trans ‐prolyl amide bond population .…”
Section: Figurementioning
confidence: 99%